Manajemen Pembiayaan Pendidikan di SD Islam Ibnu Sina Bandung - Syarif, Muhammad (STIT Fatahillah, 2025)
The purpose of the study was to determine the management of education financing, including sources, planning, implementation, organisation, and reporting system of financing at SD Islam Ibnu Sina Bandung. This research uses a qualitative approach with descriptive methods—data collection techniques through extracting information directly through interviews, observation, and documentation. The results of research on school financing management at SD Islam Ibnu Sina Bandung are well-organized and have effectively implemented the concept of effective financial management. The financing management in practice shows the data: (1) The source of education financing comes from the foundation through tuition fees, the government through BOS funds, and school businesses from canteens and cooperatives and student transport services. (2) Educational financing planning or RAPBS is carried out using a needs approach and proposals for activities from students and education personnel as well as school residents in the Ibn Sina Islamic Elementary School environment. (3) Implementation of education financing includes: financing human resources, procurement of infrastructure, maintenance of infrastructure, and teacher self-development. (4) The organisation of financing involves the principal, treasurer, operator, committee, and the foundation's finance department. (5) Financing reporting is carried out periodically according to the origin of the source of financing. Internal reporting to the Rahmatan Lil Alamin foundation is conducted monthly, while reporting to the education office is done every three months, involving the Bandung Regency education office supervisory team.